DESIGN AND INTEGRATION OF A HUMAN-ROBOT PHYSICAL INTERACTION PLATFORM WITH PURPOSES OF MEDICAL DIAGNOSIS AND REHABILITATION OF UPPER LIMB - Rosario Barrera-Gálvez; José Manuel Fernández-Ramírez; Luis E. Díaz-Pérez; José M. Busto-Villareal; Omar A. Domínguez-Ramírez (European Scientific Journal, ESJ, 2015)
In this paper a human-robot physical interaction system with purposes of diagnosis and rehabilitation of upper limb is proposed.Anunderactuatedhaptic device with six degrees of freedom is used, with low inertia and low joint friction.Adaptive control technique is used for passive haptic guidance and active exploration, in order to compensate the dynamic uncertainty of the human operator in the loop.To validate the experimental platform, a procedure is established with three steps: i) knowledge of the haptic interface (interaction with the kinematic virtual environment), ii) navigation in a virtual pipe with changes in the geometric characteristics (verification of position, velocity, collisions and runtime), and iii) haptic guidance in a structured path based on a clinical protocol (study of convergence and energy).Environmental conditions such as temperature, humidity, lighting and noise are characterizedwith purposes to define experimental conditions.In this work, we assess based on the NASA-TLX protocol,the workload perception of simple temporal-spatial tasks.